2021
DOI: 10.1177/2333794x20987781
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Injury in Neonates with Perinatal Asphyxia

Abstract: Background: Perinatal asphyxia (PA) is a major cause of morbidity and mortality in which dramatic transient impairment in liver functions occurs in some patients. Objectives: We aimed to evaluate the state of the liver in cases of Perinatal asphyxia and to assess the severity of hepatic impairment in relation to different grades of HIE. Patients and Methods: This case-control study was conducted on 100 full-term newborns with perinatal asphyxia (Group I) and 50 healthy neonates served as controls (Group II). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…Islam et al, and contradicted by some like the Elsadek et al, study, where they found no significant correlation between serum level of ALP and stages of HIE [9][10][11]. In our study, we have shown that how mortality is increased from lower to higher HIE stages (nil in HIE I to 29.42% in HIE III).…”
contrasting
confidence: 78%
See 2 more Smart Citations
“…Islam et al, and contradicted by some like the Elsadek et al, study, where they found no significant correlation between serum level of ALP and stages of HIE [9][10][11]. In our study, we have shown that how mortality is increased from lower to higher HIE stages (nil in HIE I to 29.42% in HIE III).…”
contrasting
confidence: 78%
“…This finding is similar to other studies like Elsadek et al, or Choudhury et al, where they described total protein and serum albumin significantly low in babies with perinatal asphyxia. 6,9 In the present study, levels of ALT, AST, and ALP are significantly higher among different stages of HIE, from mild to severe. However, TSB, PT, and serum albumin did not have any significant difference with increasing severity of HIE.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…All infants with coagulopathy received blood product transfusion. Elsadek et al 35 and Choudhary et al 36 addressed the issue of hepatic function impairment in hypoxic neonates and came to the same conclusion; PT and INR were markedly higher in hypoxic neonates compared with healthy ones. Mautone et al 37 found no statistically significant difference in the coagulation and fibrinolytic systems of asphyxiated and healthy neonates; platelet count, PT, aPTT, D-dimers, fibrinogen, and antithrombin III were similar between the two groups.…”
Section: Standard Coagulation Testsmentioning
confidence: 78%
“…HIE is a term to define the disturbed neurological function in the earliest days of life in the term newborn, consisting in the alteration of the level of consciousness, tone and neonatal reflexes, including the sucking and swallowing reflex, the presence of seizures in moderate and severe stages of HIE ( 5 , 8 ) and cardiovascular (bradycardia, hypotension) and respiratory disorders (irregular respiration, apnea) in severe HIE ( 5 , 9 ). Furthermore, severe HIE includes multisystem involvement, not only neurological, but also cardiac, renal, liver damage ( 4 , 5 , 10-12 ) and fluctuations in the glycemic values (generally, hypoglycemia) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%